2022
DOI: 10.3390/healthcare10050904
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Attitudes, Beliefs and Barriers to a Pulmonary Rehabilitation for COPD Patients in Saudi Arabia: A Cross-Sectional Study

Abstract: This study aimed to assess physicians’ attitudes toward delivering pulmonary rehabilitation (PR) to chronic obstructive pulmonary disease (COPD) patients and identify factors and barriers that might influence referral decisions. Between September 2021 and January 2022, a cross-sectional online survey was distributed to all physicians in Saudi Arabia. A total of 502 physicians completed the online survey, of which 62.0% (n = 312) were male. General physicians accounted for 51.2%, while internal-medicine special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“… 16 In addition, our findings are similar to previous investigations into the barriers to setting up pulmonary rehabilitation programs in Saudi Arabia, which reported that lack of capacity in medical facilities is one of the main barriers. 20 , 29 , 30 This lack in the current clinical practice indicates the need across the country to establish and formulate comprehensive CR programs that meet current international clinical guidelines. In achieving this, it is essential to note that CR could be integrated within clinical sites by employing multidisciplinary collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 In addition, our findings are similar to previous investigations into the barriers to setting up pulmonary rehabilitation programs in Saudi Arabia, which reported that lack of capacity in medical facilities is one of the main barriers. 20 , 29 , 30 This lack in the current clinical practice indicates the need across the country to establish and formulate comprehensive CR programs that meet current international clinical guidelines. In achieving this, it is essential to note that CR could be integrated within clinical sites by employing multidisciplinary collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…We used a modified version of a survey that was previously designed, created, and validated by Aldhahir et al 20–23 The questionnaire included eight closed-ended multiple-choice questions.…”
Section: Methodsmentioning
confidence: 99%
“…Reasons for not referring patients with COPD to PR programmes are likely to be multifactorial; lack of available PR centres is at top of the list, as shown in this study which is in accordance with recent study that included physicians and concluded that limited PR centres was the cause of low PR referral. 13 Saudi Arabia has a limited number of PR centres, and the number of people who can access these centres is extremely low. 9 This contrasts, for instance, with the situation in the UK, which has 228 PR services.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the referral rate was low among all physicians, which was attributed to a lack of PR centres and trained staff. 13 Given the fact that our previous study did not survey non-physicians HCPs’ attitudes, although they were implicated as a barrier to referral, the present study aimed to explore allied healthcare professionals’ attitudes and expectations towards delivering a PR programme and identify their views on factors and barriers that might influence the referral of patients with COPD in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…We used a modified version of a questionnaire that was previously designed, created, and validated by Aldhahir et al [ 17 , 18 , 19 , 20 ]. The questionnaire included eight closed-ended multiple-choice questions.…”
Section: Methodsmentioning
confidence: 99%